THE CONTROVERSIAL TOKEN CURRENCY OF MUHAMMAD BIN TUGHLUQ: A HISTORICAL ANALYSIS - Zumeer Ahmad Sofi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
In this study, an attempt has been made to explore the historical significance and legacy of the token currency introduced by Muhammad bin Tughluq during his reign as Sultan of Delhi from 1325-1351. An audacious economic reform, the token currency aimed to ease the strain on the state treasury due to expansive military campaigns and territorial expansion. Notwithstanding, the revolutionary system underpinned by copper and brass coins, intended to supplant traditional precious metals, failed due to the lack of public trust and widespread counterfeiting. Despite its failure, this experiment represented an integral part of a broader socio-economic and cultural evolution. Tughluq's reign witnessed numerous reforms and ambitious projects like the shifting of the capital to Daulatabad and extensive irrigation projects, laying the foundation for the development in the Deccan region. Lessons from this experiment, such as the necessity of public trust, a robust infrastructure, and strong security measures, continue to be relevant for contemporary monetary practices and reforms, particularly in light of debates surrounding the digitization of money and the advent of crypto currencies.